Response of Cotton Varieties to the Stage of Topping under Rainfed Condition of Bardiya, Nepal - Basnet, KB (Journal of the Institute of Agriculture and Animal Science, 2006)
A field experiment was conducted to study the impact of topping at different growth stages (3-4, 6-7, 9-10 and 12-13 sympodial branches) on productivity of two (Tamcot SP-37 and H-777) cotton varieties under rainfed condition at the Kumbher Farm (Bardiya district) of Cotton Development Board in 1995. The experiment was laid out in a Randomized Complete Block Design with four replications. The interaction effect between variety and stages of topping showed that significantly higher yield (1.23 t/ha) was produced by topping plants at the stage of 12-13 sympodial banches of the variety Tamcot SP-37 as compared to all other treatments. At all stages of topping the yield produced by Tamcot SP-37 was significantly higher than H-777. The average seed cotton yield (1.03 t/ha) of Tamcot SP-37 was significantly higher than that of H- 777 (0.71 t/ha) and the difference in yield was 45.0%. The seed-cotton yield increased from 0.75 to 1.00 t/ ha with the postponed of topping from 3-4 to 12-13 sympodial branches, but significant difference was recorded between late (12-13 sympodial branches) and early (3-4 and 6-7 sympodial branches) stages of topping. Thus, for rainfed condition of Bardiya Tamcot SP-37 was a suitable variety with 12-13 sympodial branches as an appropriate stage of topping for sustainable production of cotton. Key words: Variety, topping, sympodial branches. J. Inst. Agric. Anim. Sci. 27:165-168 (2006)